2003
DOI: 10.1038/sj.onc.1206203
|View full text |Cite
|
Sign up to set email alerts
|

α6β1 integrin induces proteasome-mediated cleavage of erbB2 in breast cancer cells

Abstract: ErbB2 and a6 integrin have been implicated in malignancy of breast cancer cells. Here we have determined the influence of a6b1 integrin on erbB2 signaling in anchorage-independent growth, using MDA-MB435 breast cancer cells. Firstly, we transfected the cells with erbB2 cDNA, and isolated cells with high or low levels of a6b1 integrin by cell sorting (a6H-ErbB and a6L-ErbB). We found that an erbB ligand, heregulin b1, enhanced growth activity of a6L-ErbB cells, but not a6H-ErbB cells. Secondly, we established c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…HSP90 inhibition also induces cleavage of the cytoplasmic part of ErbB2, resulting in a transmembrane 135-kDa ErbB2 and short-lived cytoplasmic fragments (Tikhomirov and Carpenter, 2000;Lerdrup et al, 2006). The cleavage occurs in the kinase domain and a similar cleavage is seen after stimulation with curcumin or staurosporine (Tikhomirov and Carpenter, 2001) or in cells with high levels of ␣6␤1 integrin (Shimizu et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…HSP90 inhibition also induces cleavage of the cytoplasmic part of ErbB2, resulting in a transmembrane 135-kDa ErbB2 and short-lived cytoplasmic fragments (Tikhomirov and Carpenter, 2000;Lerdrup et al, 2006). The cleavage occurs in the kinase domain and a similar cleavage is seen after stimulation with curcumin or staurosporine (Tikhomirov and Carpenter, 2001) or in cells with high levels of ␣6␤1 integrin (Shimizu et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…HSP90 inhibition also induces cleavage of the cytoplasmic part of ErbB2, resulting in a transmembrane 135-kDa ErbB2 and short-lived cytoplasmic fragments (Tikhomirov and Carpenter, 2000;Lerdrup et al, 2006). The cleavage occurs in the kinase domain and a similar cleavage is seen after stimulation with curcumin or staurosporine (Tikhomirov and Carpenter, 2001) or in cells with high levels of ␣6␤1 integrin (Shimizu et al, 2003).It has remained elusive whether endocytosis and C-terminal cleavage of ErbB2 are independent or correlated events. If positively correlated, C-terminal cleavage of ErbB2 could promote endocytosis by releasing ErbB2 from a retention mechanism that normally sequesters the receptor at the plasma membrane (Sorkin et al, 1993;Hommelgaard et al, 2004;Lerdrup et al, 2006) or by exposure of an unknown cryptic motif stimulating endocytosis.…”
mentioning
confidence: 99%
“…Increasing evidence suggests an interplay between HER-2 and integrins (19,20), a large family of cell surface heterodimeric receptors composed of α and β subunits (21). The β 1 subunit, which is encoded by the ITGB1 gene (also known as CD29 and VLAB), plays a major role in mediating cell-ECM interactions (22) and druginduced (23)(24)(25) or radiation-induced resistance (26), as well as in tumor initiation (27), progression, and invasion (22).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, increased expression of β 1 -integrin was associated with poor prognosis in patients with small-cell lung cancer (28), melanoma (29), and invasive breast cancer (30). Several arguments support the tenet that the deleterious effects of increased β 1 -integrin expression merit further investigation in the context of HER-2-positive breast cancer, notably, (a) binding of β 1 -integrin to ECM induces similar downstream signaling pathways to HER-2 (31), such as the PI3K/ Akt and extracellular signal-regulated kinase1/2 (ERK1/2) pathways (32); (b) reciprocal interactions (i.e., cross-talk) between HER-2 and integrins were reported in different cell types (19,20); (c) β 1 -integrin is overexpressed in JIMT-1 (33), a HER-2-positive breast cancer cell line isolated from a patient who did not respond to trastuzumab (34). Nonetheless, the prognostic relevance of β 1 -integrin expression in HER-2-positive breast cancer specimens and the functional consequences of its level of expression have not been investigated with respect to trastuzumab response.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence supporting this explanation has yet to be reported. On the other hand, a recent study in breast cancer cells showed that 61 integrin inhibits HER2 signals by inducing proteasome-dependent proteolytic cleavage of the HER2 cytoplasmic domain [46]. Since the antibody that we used labels the cytoplasmic domain of the HER2 molecule, this proteolytic cleavage may cause a low immunoreaction for HER2 in the basal layer.…”
Section: Discussionmentioning
confidence: 84%